Analisis Pengaruh CSR, GCG, serta Ukuran Perusahaan terhadap Kinerja Keuangan pada Perusahaan Perbankan di BEI Periode Tahun 2015-2019 - Risal Rinofah; Ratih Kusumawardhani; Pramudhita Annisa Ramadhani (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
The purpose of this study is to find out the effect of Corporate Social Responsibility (CSR), Good Corporate Governance (GCG), and Company Size on Financial Performance in Banking Companies listed on the IDX in the 2015-2019 period. The variables used in this study are Corporate Social Responsibility (CSR), Good Corporate Governance (GCG), and Company Size as independent variables, while the dependent variable is Financial Performance. This type of research is descriptive research with a quantitative approach. The subjects of this research are banking companies listed on the Indonesia Stock Exchange for the 2015-2019 period. Secondary data was obtained from the annual reports of 9 companies by purposive sampling. Then the data were analyzed by using multiple linear regression technique. The results of the study using the t-test showed that the Corporate Social Responsibility (X1) variable had a significant effect on Financial Performance (Y) with a significance value of 0.000 <0.05; Good Corporate Governance variable (X2) has no significant effect on Financial Performance (Y) with a significance value of 0.085 <0.05; Firm Size variable (X3) has a significant effect on Financial Performance (Y) with a significance value of 0.009 <0.05. Keywords: Corporate Social Responsibility; Good Corporate Governance; Company Size; Financial performance.